Severe Corticosteroid-Induced Ocular Hypertension Requiring Bilateral Trabeculectomies in a Patient with Takayasu’s Arteritis - Anna Maria Gruener; Pranev Sharma; Sally Ameen; Faisal Ahmed (Case Reports in Ophthalmological Medicine)
We present a rare case of severe corticosteroid-induced ocular hypertension (OHT) after prolonged systemic corticosteroid use in a young woman with Takayasu’s arteritis. As she did not sufficiently respond to ocular antihypertensive therapies, bilateral enhanced trabeculectomies were required to normalize her intraocular pressures. The systemic side effects of corticosteroids are well known, yet steroid-induced OHT and glaucoma remain silent causes of ocular morbidity. This case highlights the importance of IOP-monitoring in visually asymptomatic patients on systemic corticosteroids. It further emphasizes the need to raise awareness of the potential ocular side effects of steroids amongst physicians, in particular those looking after patients with autoimmune and inflammatory diseases.